2015
DOI: 10.1097/eja.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the minimum initial intrathecal dose of isobaric 0.5% bupivacaine for the surgical repair of a proximal femoral fracture

Abstract: Clinicaltrials.gov identifier: NCT01680120.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The injection time the mixture is given may have an effect on the hypotension severity and we await studies addressing this topic. In an interesting study by Szucs et al 29 they used the "up-and-down" method described by Dixon and Massey in 1969 to find the lowest intrathecal dose of local anesthetic to provide adequate anaesthesia for a hip fracture operation. 30 They concluded that 0.24 mL of 5 mg/mL isobaric bupivacaine was enough as a single dose but still recommended a dose of 0.4 mL or more i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The injection time the mixture is given may have an effect on the hypotension severity and we await studies addressing this topic. In an interesting study by Szucs et al 29 they used the "up-and-down" method described by Dixon and Massey in 1969 to find the lowest intrathecal dose of local anesthetic to provide adequate anaesthesia for a hip fracture operation. 30 They concluded that 0.24 mL of 5 mg/mL isobaric bupivacaine was enough as a single dose but still recommended a dose of 0.4 mL or more i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The injection time the mixture is given may have an effect on the hypotension severity and we await studies addressing this topic. In an interesting study by Szucs et al 30 they used the “up-and-down” method described by Dixon and Massey in 1969 to find the lowest intrathecal dose of local anesthetic to provide adequate anaesthesia for a hip fracture operation. 31 They concluded that 0.24 mL of 5 mg/mL isobaric bupivacaine was enough as a single dose but still recommended a dose of 0.4 mL or more i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The injection time the mixture is given may have an effect on the hypotension severity and we await studies addressing this topic. In an elegant study by Szucs et al [27] they used the method "up-and-down" described by Dixon and Massey in 1969 to find the lowest intrathecal dose of local anesthetic to provide adequate anesthesia for a hip fracture operation [28]. They concluded that 0.24 ml of 5 mg/ml isobaric bupivacaine was enough as a single dose but still recommended a dose of 0.4 ml or more i.e.2 mg.…”
Section: Discussionmentioning
confidence: 99%